Kompetensi PTK Guru pada MIN Nagan Raya - Junias Zulfahmi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
This research study about the competence of PTK teachers at MIN Nagan Raya, with a purpose to know the capability of teachers in carrying out PTK. The Methods used in this research is a qualitative yield descriptive data. While that was to become the informants in this research was PAI teachers who have grade III/d or teachers who have been teaching for a long time in PAI. While the data collection used in this research include observations, interviews, and document analysis. The result of this study shows that any response or teacher perception against PTK was teachers have become painfully aware that the program PTK is a program that is organized by the government. Teachers received or agree with PTK program. Because generally, PTK is essential in addition to teaching teachers should be able for research to improve the condition of his class according to the rules or demands in education. While the capability of teachers in carrying out, in general, is still low, the average teachers only know and understand glimpses of the concept of PTK, so constrained in practice. That condition needs to get serious attention from the head of Madrasah, the official ministry of religion Nagan Raya and other stakeholders to give training programs, guidance, and facilities